An Analysis of Survival in Haploid and Diploid Cell Cultures after Exposure to ICR Acridine Half-mustard Compounds Mutagenic for Bacteria - Mezger-Freed, Liselotte (1974)
Population changes induced by acridine mustards in haploid and diploid cultured cell lines from Rana pipiens were compared to test the expectation that recessive mutations will be expressed in diploid cells with a frequency equal to the square of that in haploid cells, and to investigate the usefulness of such comparison for the screening of possible mutagens. The differences in survival frequency after treatment were much smaller than predicted on the basis of the expression of lethal (recessive) mutations alone. Survival was also affected by culture conditions, drug-resistance phenomena, and other cell properties. It is suggested that with the evolution of epigenetic processes for the production of stable phenotypes, the vertebrate cell also acquired more efficient means to prevent the expression of gene mutation and that the acridine compounds may affect both epigenetic and genetic changes.